2016
DOI: 10.1136/medethics-2016-103683
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of conducting prospective observational research on critically ill, dying patients in the intensive care unit

Abstract: Studying patients during the end of life is important, as it has the potential to lead to improvements in care for the dying. For patients who die after a controlled withdrawal of life-sustaining therapies in the intensive care unit, information about the natural history of death and the process of removing life support has additionally led to advances in practice for deceased organ donation. However, this unique population of severely critically ill and imminently dying patients has been difficult to study, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
(19 reference statements)
1
17
0
Order By: Relevance
“…All interviews will be conducted between 6 and 8 weeks after the patient’s death to minimise family burden, optimise research consent rates and avoid influencing the donation process. This approach was successful in previous studies involving bereaving families20–23 and is supported by our patient partners.…”
Section: Methods and Analysissupporting
confidence: 57%
“…All interviews will be conducted between 6 and 8 weeks after the patient’s death to minimise family burden, optimise research consent rates and avoid influencing the donation process. This approach was successful in previous studies involving bereaving families20–23 and is supported by our patient partners.…”
Section: Methods and Analysissupporting
confidence: 57%
“…This review also does not extend to prospective research on deceased donation after circulatory death, for which prospective organ donors are alive at the time of research enrollment. At present, there are exceedingly few studies of donor management in this clinical situation (Levvey et al, 2008;Suntharalingam et al, 2009;Wind et al, 2012). Some authors have postulated that consenting to research may confer benefits to the family of organ donors by aiding them with the grieving process (van Beinum et al, 2017), and these investigators have qualitative research to address this hypothesis underway.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are exceedingly few studies of donor management in this clinical situation (Levvey et al, 2008; Suntharalingam et al, 2009; Wind et al, 2012). Some authors have postulated that consenting to research may confer benefits to the family of organ donors by aiding them with the grieving process (van Beinum et al, 2017), and these investigators have qualitative research to address this hypothesis underway. This review did not address challenges related to the consent of organ recipients in relation to research of neurologically deceased donors.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have clearly shown the feasibility of high-quality research in this area. 6,24,25 A summary of the generated research agenda can be found in eAppendix 9, available as ESM.…”
Section: Discussionmentioning
confidence: 99%